Request a call back

Join NOW to get access to exclusive study material for best results

CBSE Class 10 Answered

prove that
Asked by | 06 Jun, 2008, 07:32: PM
Expert Answer

1/(cosecA-cotA)

= 1/ [(1/sinA)-(cosA/sinA)]

= 1/ [(1-cosA)/sinA]

= sinA/(1-cosA)

= sinA(1+cosA)/(1-cosA)(1+cosA)

= (sinA+sinAcosA)/(1-cos2A)

= (sinA+sinAcosA)/sin2A

= sinA/sin2A + sinAcosA/sin2A

= 1/sinA + cosA/sinA

= cosecA + cotA

Answered by | 07 Jun, 2008, 08:25: PM
CBSE 10 - Maths
Asked by nikunjgupta102021 | 12 Jul, 2021, 09:01: AM
ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by arindeep.singh | 02 Oct, 2020, 12:19: PM
ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by arindeep.singh | 02 Oct, 2020, 12:19: PM
ANSWERED BY EXPERT
Free Sample Papers - Click Here
×